Analysis of Students’ Sustainability Consciousness Based on Conceptual Dimensions, Determinant Factors, and the Knowledge–Attitude–Behavior Gap: A Systematic Literature Review - Islawati Islawati; Eli Rohaeti; Erfan Priyambodo (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze students’ sustainability consciousness based on its conceptual dimensions, determinant factors, and the relationships among knowledge, attitudes, and behavior. This study employed a systematic literature review (SLR) approach, guided by the PRISMA framework to ensure a structured and transparent process of literature identification, screening, and synthesis. The literature search was conducted using the Scopus database with keywords such as “sustainability consciousness in higher education,” “students’ environmental awareness,” and “sustainability consciousness among university students.” The initial search yielded 249 records, of which 24 articles met the inclusion criteria and were included in the final analysis. The findings indicate that sustainability consciousness is a multidimensional construct consisting of knowledge, attitudes, and behavior that interact dynamically. The knowledge dimension is generally higher than the behavioral dimension, indicating a gap between students’ understanding and their actual practices. In addition, sustainability consciousness is influenced by internal factors such as environmental literacy and individual values, as well as external factors including education, curriculum, campus environment, and pedagogical approaches. The relationships among these dimensions are complex and non-linear, mediated by variables such as social norms and learning experiences. A key finding is the presence of a knowledge–action gap, demonstrating that increased knowledge does not necessarily lead to sustainable behavior. This study contributes by integrating the dimensions, determinants, and relationships of sustainability consciousness into a comprehensive analytical framework.